Karakteristik Fisik dan Aktivitas Antibakteri Sabun Cair Minyak Nilam (Pogostemon cablin Benth.) yang Berbasis Surfaktan Sodium Lauril Eter Sulfat - Anggraeni, Yuni; Nisa', Fakhrun; Betha, Ofa Suzanti (Jurnal Kefarmasian Indonesia, 2020)
Patchouli oil obtained from patchouli plants (Pogostemon cablin Benth.) has been widely used as an antibacterial agent in liquid and solid soap preparation. In this research, patchouli oil was added to liquid soap formula which use sodium lauryl ether sulphate (SLES) surfactant. The purpose of this study was to determine the physical characteristics and antibacterial activity of patchouli oil liquid soaps based on SLES surfactant. The Liquid soaps were prepared into four formulas with variation of patchouli oil concentration that were F0 (0.00% w/w), F1 (0.05% w/w), F2 (0.50% w/w), and F3 (1.00% w/w). The liquid soaps were evaluated including organoleptic, microscopic property, physical stability by using centrifuge test, pH, foam height and stability, viscosity and rheology, and antibacterial activity against Staphylococcus aureus ATCC 25923 by using disc diffusion method and chloramphenicol as a positive control. The results showed that all liquid soap formulas had following characteristics: translucent except F3 slightly murky, homogen, stable after centrifuge test, pH between 6.55 – 6.66 that were no significantly different and met SNI standards of liquid soap, foam height between 2.67 – 3.23 cm that were no significantly different and stable after 5 minutes of testing, viscosity between 2237 – 2397 cPs relatively equal in all formulas with pseudoplastic rheological properties. The patchouli oil liquid soaps had antibacterial activity against Staphylococcus aureus ATCC 25923, where F0, F1, F2, F3 and positive control result in inhibition zone diameter of 11.26±2.60 mm, 14.60 ± 2.45mm, 15.51 ± 0.44 mm, 17.97 ± 0.71 mm and 19.00 ± 3.92 mm respectively. Based on the ANOVA one way test, the addition of 1% patchouli oil gave a significant effect on the inhibition zone diameter compared to F0 (without patchouli oil)